Identification of Tourism Product Marketing Strategy Plans to Foreign Markets Efforts to Increase Income in the Era of Regional Autonomy - Sri Aprianti Tarigan; Juliana Juliana; Tina Linda; Bestadrian Prawiro Theng; Edward Harnjo (Budapest International Research and Critics University, 2021)
This tourism study analyzed the evidence of studies to identify marketing strategies for tourism products to foreign markets through the study and analysis of several international publications that discuss tourism promotion and marketing issues. The tourism business is the same as other businesses where it is very much tied to promotion and marketing in order to be able to survive and develop quickly to be known by potential foreign tourists. Therefore, we collected literature with the help of internet searches on some well-known publications such as Sagepub, Google Scholar, and other publications published in the last ten years. Then we analyzed it with a phenomenological approach starting from the data coding system, interpretation and evaluation until we found data findings that answered the core problem of this tourism study with the principle of high validity. Because this study depends on the literature, all of our data is found electronically following health protocol where there are public restrictions on Covid-19 response efforts. Based on the data and discussion, we conclude that the findings include tourism promotion and marketing strategies based on experts, an innovative and productive way to believe via the internet with several social media platforms and other websites. Thus, this finding becomes a significant contribution for many people.